Exploring Glucagon-like peptide-1 as a Target Protein for Diabetes Mellitus Treatment: Molecular Docking and Pharmacokinetic Analysis of Phytocompounds from Momordica charantia - Dishant Chandgude (International Journal of Biochemistry and Biomolecule Research, 2024)
Objective: This study aimed to use molecular docking techniques to explore the potential of GLP-1 (glucagon-like peptide-1) as a target protein for the treatment of diabetes mellitus, a chronic metabolic disease marked by elevated blood glucose levels. Given its crucial role in maintaining insulin secretion and glucose homeostasis, GLP-1 may serve as a future target for diabetes therapy. Method: The study employed a multi-phase method. Initially, protein extraction was carried out using the Protein Data Bank ID 3C59 for GLP-1. The extracted structure was then verified through secondary structure prediction and Ramachandran Plot analysis to ensure its reliability. Phytocompounds from "Momordica charantia" were obtained using the IMPPAT Database. An ADME study was conducted to evaluate the pharmacokinetic characteristics of these compounds, including their absorption, distribution, metabolism, and excretion profiles. Molecular docking was then performed using PyRx to assess the binding affinity and interaction patterns between GLP-1 and the identified phytocompounds. The 3D and 2D interaction structures were subsequently examined using BIOVIA Discovery Studio to visualize the binding interactions and to identify key amino acid residues involved. Result: The molecular docking study identified diosgenin, alpha-spinasterol, and momordicoside I as potential drug candidates capable of modulating the activity of GLP-1. These compounds exhibited strong binding affinities and favorable interaction patterns with the GLP-1 protein. Conclusion: The study suggests that GLP-1 is a promising target for diabetes treatment, demonstrating favorable molecular interactions with phytocompounds derived from Momordica charantia. Structural validation and ADME analysis further support the potential efficacy of these compounds. These findings could lead to the development of new therapeutic approaches for managing diabetes, highlighting the significance of GLP-1 in diabetes therapy.
Keywords: ADME analysis; GLP-1; Momordica charantia; diabetes treatment; molecular docking; phytocompounds; structural validation